Sofia, design and implementation of a virtual assistance agent for attention a financial institution [Sofia, diseño e implementacion de un agente de atención virtual para una entidad financiera] (2018)
Different systems of human-machine interaction with capacities more and more similar to humans are diffused and generate different perspectives of incorporation in organizations. A growing trend is the construction of artificial intelligence software to execute tasks without human intervention, such as collecting and presenting information to users, making a reservation at a restaurant on a special date, and generally carrying out tasks related to customer service by automated bots for solving to solve everyday situations, normally employees in the messaging through the development of advanced conversational interfaces. The bots with the ability to simulate conversations through conversational interfaces are already a reality and their boom is increasing. A field where they have a prominent presence has to do with customer service. This paper presents the components designed and developed of a bot used by a company in the financial sector consolidated for more than a decade in Latin America to manage customer service in order to solve everyday situations. © 2018 AISTI.